CAÁ - Cultivo Amigo de las Aves. El sabor de la selva - Cinto, Juan Pablo; Gil, Guillermo; Lozano, Damián; Barutta, Gustavo; Tarnoski, Sergio (Revista Aves Argentinas, 2023)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).